FFAR1/GPR40: One target, different binding sites, many agonists, no drugs, but a continuous and unprofitable tug-of-war between ligand lipophilicity, activity, and toxicity. (1st June 2021) - Governa, Paolo; Caroleo, Maria Cristina; Carullo, Gabriele; Aiello, Francesca; Cione, Erika; Manetti, Fabrizio
Graphical abstract: Abstract: The progress made so far in the elucidation of the structure of free fatty acid receptor 1 (FFAR1) and its secondary and ternary complexes with partial and full allosteric ligands led to the discovery of various putative binding regions on the FFAR1 surface. Attempts to develop FFAR1 agonists culminated with the identification of TAK-875 (1 ), whose phase 3 clinical trials were terminated due to potential liver toxicity. In the search of safer agonists, numerous classes of new compounds were designed, synthesized, and tested. Chemical decoration of the scaffolds was rationalized to reach a good balance between lipophilicity, activity, and toxicity. Today, targeting FFAR1 with positive modulators represents an attractive pharmacological tool for the treatment of type 2 diabetes mellitus (T2DM), mainly because of the lack of hypoglycaemic side effects associated with several antidiabetic drugs currently available. Moreover, considering the involvement of FFAR1 in many physio-pathological processes, its agonists are also emerging as possible therapeutic tools for alleviating organ inflammation and fibrosis, as well as for the treatment of CNS disorders, such as Alzheimer's disease and dementia.